PENGEMBANGAN KREATIVITAS MASYARAKAT DESA SAMBELIA DALAM PEMBERDAYAAN EKONOMI KREATIF MELALUI PENGOLAHAN KERIPIK JAGUNG DENGAN PROSES SEDERHANA - Pathurahman, Pathurahman; Mir’atussholiha, Baiq Khovifa; Widodo, Mardaniel Roikhan; Aulia, Anggun Yesi; Nurmawanti, Nunung; Ningsih, Sarlin Ayu; Islamy, Randa; Humaeroh, Hasmi Laela; Wardana, Aldi Bagustia; Ferawati, Ferawati; MZ, Rizki Ramandaris (Jurnal Wicara, 2023)
Creative economy empowerment for the community is needed to solve problems, especially in the aspect of abundant harvests. Creative economy is local-based economic development carried out by increasing the selling value of local products so as to increase community income. Therefore, we motivate the community to be able to utilize the harvest into creativity that aims to provide opportunities, development, and development of life welfare, create jobs and independence in building a decent and sufficient life and utilize the potential of the village from abundant harvests to improve the economy. The method used is community-oriented with an approach in development that can realize the order of social life where the actors and determinants of development are the community itself. Based on the research found, we and the community have a decision to make better use of the harvest to improve the quality of life. Creative economy community empowerment aims to provide opportunities for development and development of life welfare, the creation of employment and independence in building a decent and sufficient life and utilizing the potential of abundant harvests to improve the economy of rural communities.